Doped phosphate positive electrode material and preparation method and application thereof
By doping titanium and molybdenum elements into the lithium iron phosphate positive electrode material, the structure and conductivity of the lithium iron phosphate positive electrode material is solved, and the dynamic performance and cycle stability of the battery are significantly improved .
Patent Information
- Application Number
- CN202411500865.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-03
AI Technical Summary
The existing lithium iron phosphate positive electrode materials have low electronic conductivity and small lithium ion diffusion coefficient, which limits their application in lithium-ion batteries.
By doping metal elements such as titanium and molybdenum into the lithium iron phosphate lattice, precursor mixture is prepared by liquid phase method, and primary sintering and secondary sintering treatments are performed to optimize the structural stability and compression modulus of the material, and improve ions and Electronic conductivity.
It significantly improves the electronic conductivity, lithium ion diffusion coefficient and cyclic stability of the positive electrode material, extends the cycle life of the battery, and improves the energy density and power density.
Smart Images

Figure CN119252903A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a doped phosphate-based positive electrode material and a preparation method and application thereof. Background Art
[0002] With the gradual promotion of clean energy, lithium-ion batteries are widely used in new energy vehicles, energy storage power stations and other fields due to their high energy density, long cycle life and environmental protection. Among them, the positive electrode material is a key component of lithium-ion batteries, and its performance directly determines the overall performance of the battery. Lithium iron phosphate is a commonly used positive electrode material for lithium-ion batteries, but its low electronic conductivity, small lithium ion diffusion coefficient and low compaction density limit the application of lithium iron phosphate in the field of power batteries.
[0003] To solve the above problems, metal element doping is used to improve the electronic conductivity and lithium ion diffusion coefficient of lithium iron phosphate. For example, high-valent elements such as cobalt, nickel, and manganese are doped into the lithium iron phosphate lattice. However, after the above elements are doped, while improving some of the performance of lithium iron phosphate, they will also sacrifice other performances. For example, although manganese doping can improve the working voltage and energy density of lithium iron phosphate, it will significantly reduce the electronic conductivity.
[0004] Therefore, it is of great significance to promote the development of lithium-ion batteries to prepare phosphate-based positive electrode materials with high electronic conductivity and lithium ion diffusion coefficient and stable structure and improve their comprehensive performance. Summary of the invention
[0005] The purpose of the present application is to provide a doped phosphate-based positive electrode material and a preparation method and application thereof, aiming to solve the problems of low electronic conductivity and small ion diffusion coefficient of existing phosphate-based positive electrode materials to a certain extent.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In the first aspect, the present application provides a doped phosphate-based positive electrode material, comprising a phosphate-based active material and a doped metal element doped in the crystal structure of the phosphate-based active material; under a pressure of 100MPa to 500MPa, the maximum deformation of the particles of the doped phosphate-based positive electrode material is less than 50%, and the reversible deformation is less than 10%.
[0008] In a second aspect, the present application provides a method for preparing a doped phosphate-based positive electrode material, comprising the following steps:
[0009] Obtaining raw material components and a doping metal source for preparing a phosphate-based active material, and preparing a precursor mixture by a liquid phase method using the raw material components and the doping metal source;
[0010] In an inert atmosphere, the precursor mixture is sintered once and then crushed and sintered twice to obtain a doped phosphate-based positive electrode material; under a pressure of 100MPa to 500MPa, the maximum deformation of the particles of the doped phosphate-based positive electrode material is less than 50%, and the reversible deformation is less than 10%.
[0011] In a third aspect, the present application provides an application of a doped phosphate-based positive electrode material, wherein the above-mentioned doped phosphate-based positive electrode material or the doped phosphate-based positive electrode material prepared by the above-mentioned method is applied to a positive electrode sheet and / or a secondary battery.
[0012] The doped phosphate positive electrode material provided in the first aspect of the present application optimizes the structural stability of the doped phosphate positive electrode material by doping metal elements in the crystal structure of the phosphate active material. The maximum deformation of the particles of the doped phosphate positive electrode material is less than 50% and the reversible deformation is less than 10% under a pressure of 100MPa to 500MPa. The compression modulus of the positive electrode material is improved. The larger the reversible deformation, the more conducive it is to alleviate the mechanical stress caused by the volume expansion of the material during the process of lithium removal and lithium insertion, increase reversibility, and thus help improve the cycle performance and durability of the battery, enhance the safety of the battery, and also help to improve the stability of ion and electron transmission in the positive electrode material, so that it has a longer cycle life. In addition, by doping with metal elements, while improving the compression modulus of the positive electrode material, it is also possible to change the chemical composition and electronic structure of the surface of the positive electrode material, improve the ion and electronic conductivity of the material, and thus improve the energy density and power density of the battery.
[0013] The second aspect of the present application provides a method for preparing a doped phosphate-based positive electrode material, in which the raw material components and a doped metal source including a titanium source and a molybdenum source are prepared into a precursor mixture by a liquid phase method, and then, a primary sintering, a pulverizing and a secondary sintering treatment are sequentially performed in an inert gas, so that the doped metal elements are doped into the lattice of the phosphate-based active material to obtain a doped phosphate-based positive electrode material. In the liquid phase system adopted, the raw materials are fully mixed and the stoichiometry is controllable, which is conducive to the doping of the doped metal elements into the lattice of the phosphate-based active material. The two sintering and pulverizing processes are beneficial to improving the sintering efficiency, controlling the material particle size and improving the uniformity. The preparation process of the present application is simple and suitable for industrial large-scale production and application. The prepared doped phosphate positive electrode material optimizes the structure of the doped phosphate positive electrode material by doping metal elements in the crystal structure of the phosphate active material, improves the structural stability and compression modulus of the doped phosphate positive electrode material, and can change the chemical composition and electronic structure of the surface of the positive electrode material, so that the doped phosphate positive electrode material has higher ionic conductivity, electronic conductivity, gram capacity, cycle stability and other characteristics.
[0014] The doped phosphate-based positive electrode material provided in the third aspect of the present application has high electronic conductivity, ion diffusion coefficient, crystal structure stability, charge and discharge cycle stability, capacity and other characteristics, and can be directly applied to positive electrode sheets, and can also be further applied to secondary batteries to improve the charge and discharge specific energy, discharge platform, cycle capacity retention rate, rate performance and other properties of positive electrode sheets and secondary batteries, and comprehensively improve the battery's kinetic performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0016] Figure 1 It is a schematic diagram of a process for preparing a doped phosphate-based positive electrode material provided in an embodiment of the present application;
[0017] Figure 2 is a SEM image of the doped phosphate-based positive electrode material provided in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present application;
[0018] Figure 3 It is the XRD spectrum of the doped phosphate-based positive electrode material provided in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0020] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0021] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0022] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0023] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0024] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.
[0025] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0026] The term "compression modulus" means compression modulus in English, also known as compression modulus or unconfined deformation modulus, which describes the ratio of vertical compressive stress to vertical total strain of doped phosphate cathode materials when they cannot be deformed laterally at all, and is represented by the symbol Es. It is an important indicator to measure the compressibility of doped phosphate cathode materials.
[0027] A first aspect of an embodiment of the present application provides a doped phosphate-based positive electrode material, comprising a phosphate-based active material and a doped metal element doped in the crystal structure of the phosphate-based active material; under a pressure of 100MPa to 500MPa, the maximum deformation of the particles of the doped phosphate-based positive electrode material is less than 50%, and the reversible deformation is less than 10%.
[0028] The doped phosphate-based cathode material provided in the first aspect of the embodiment of the present application optimizes the structure of the doped phosphate-based cathode material by doping metal elements in the crystal structure of the phosphate-based active material, and improves the crystal structure stability of the material. The maximum deformation of the particles of the doped phosphate-based cathode material is less than 50% and the reversible deformation is less than 10% under a pressure of 100MPa to 500MPa. The structural stability and compression modulus of the doped phosphate-based cathode material are significantly improved. The larger the compression modulus, the smaller the irreversible deformation and the maximum deformation. The difference between the irreversible deformation and the maximum deformation is the reversible deformation. Within a certain range, the larger the reversible deformation, the better. The larger the reversible deformation, the more conducive to alleviating the mechanical stress caused by the volume expansion of the material during the process of lithium removal and lithium insertion, increasing reversibility, and thus helping to improve the cycle performance and durability of the battery, enhance the safety of the battery, and also help to improve the stability of ion and electron transmission in the cathode material, so that it has a higher compaction density, stronger anti-polarization ability, and longer cycle life. Moreover, by doping with metal elements, while improving the compression modulus of the positive electrode material, it is also possible to change the chemical composition and electronic structure of the positive electrode material surface, thereby improving the ionic and electronic conductivity of the material, thereby increasing the energy density and power density of the battery, and extending the battery's cycle life and anti-interference ability.
[0029] Exemplarily, the pressure condition can be 100MPa, 200MPa, 300MPa, 400MPa, 500MPa, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the maximum deformation amount of a single particle of the doped phosphate-based positive electrode material can be 49%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the reversible deformation amount can be 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1.5%, 1%, 0.5%, 0.3%, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values.
[0030] In some possible implementations, under the condition that the pressure of the doped phosphate-based positive electrode material is 100MPa to 400MPa, the maximum deformation of the particles is 20% to 30%, and the reversible deformation is 1.5% to 5%. In this case, the doped phosphate-based positive electrode material has better lattice stability and compression modulus. The larger the compression modulus, the smaller the irreversible deformation and the maximum deformation, and the difference between the irreversible deformation and the maximum deformation is the reversible deformation. Within a certain range, the larger the reversible variable, the better. The larger the reversible deformation, the more conducive to alleviating the mechanical stress caused by the volume expansion of the material during the process of lithium removal and lithium insertion, and increasing reversibility. This is more conducive to improving the cycle performance and durability of the battery, enhancing the safety of the battery, and also helping to improve the stability of ion and electron transmission in the positive electrode material, so that it has a higher compaction density, stronger anti-polarization ability, and longer cycle life.
[0031] In some possible implementations, the doped metal element includes at least one of V, Ti, Mo, and Mg. These metal elements are doped into the crystal structure of the phosphate-based active material, which can improve the structural stability of the doped phosphate-based positive electrode material, improve the compression modulus of the positive electrode material, and change the chemical composition and electronic structure of the surface of the positive electrode material, thereby improving the ionic and electronic conductivity of the material.
[0032] In some possible implementations, the phosphate-based active material contains iron, and the doping metal element is doped in the iron site of the phosphate-based active material. In this case, the electrochemical performance and structural stability of the phosphate-based active material can be better optimized.
[0033] In some possible implementations, the doped metal elements include titanium and molybdenum. In some possible implementations, the doped metal elements include titanium and molybdenum, which are doped in the iron site of the phosphate active material. In this case, the iron site is doped with titanium and molybdenum at the same time, wherein titanium doped in the iron site can reduce the unit cell volume of the phosphate active material, shorten the lithium ion transmission path, thereby improving the electronic conductivity and ion diffusion rate of the doped phosphate positive electrode material, improving battery polarization, and increasing energy efficiency. Molybdenum doped in the iron site can improve the isotropy of the phosphate positive electrode material, improve the compression modulus and lattice stability, and then make the particles more round, more reversible, and more able to alleviate the mechanical stress caused by the volume expansion of the material during the process of lithium removal and lithium insertion, thereby improving the energy density and cycle stability of the battery; through the synergistic effect of doped titanium and molybdenum, the band structure and electronic state density of the positive electrode material can be significantly affected, the ion and electron transmission rate can be improved, the lattice stability, the isotropy and reversibility of the material can be improved, and the electrochemical performance of the phosphate positive electrode material can be comprehensively improved.
[0034] In some possible implementations, the molar ratio of iron, titanium and molybdenum in the iron site of the crystal structure of the doped phosphate-based positive electrode material is (0.94-0.98): (0.01-0.04): (0.01-0.02). In this case, the content of titanium and molybdenum doped in the iron site of the phosphate-based active material fully ensures the improvement of the conductivity and ion diffusion rate of the doped phosphate-based positive electrode material, as well as the improvement of the isotropy, compression modulus and lattice stability of the phosphate-based positive electrode material. Illustratively, in the iron site of the crystal structure of the doped phosphate-based positive electrode material, the molar ratio of iron, titanium and molybdenum can be 0.98:0.01:0.01, 0.97:0.02:0.01, 0.97:0.01:0.02, 0.96:0.01:0.03, 0.96:0.02:0.02, 0.95:0.01:0.04, 0.95:0.02:0.03, 0.94:0.02:0.04, or the like, typical but non-limiting ratios of any point value or an interval value between any two point value ratios.
[0035] In some possible implementations, in the doped phosphate-based positive electrode material, the particle size D10 of the particles is 0.20 μm to 0.80 μm, the particle size D50 is 0.8 μm to 3.2 μm, the particle size D90 is 2 μm to 11 μm, and the particle size D99 is 3 μm to 20 μm. Exemplarily, the particle size D10 of the particles can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.61 μm, 0.618 μm, 0.62 μm, 0.63 μm, 0.64 μm, 0.65 μm, 0.66 μm, 0.669 μm, 0.67 μm, 0.68 μm, 0.69 μm, 0.70 μm, 0.80 μm, etc., which are typical but Non-limiting arbitrary point value or interval value between any two point values; particle size D50 can be 0.8μm, 1μm, 1.5μm, 1.6μm, 1.67μm, 1.7μm, 1.8μm, 1.87μm, 1.9μm, 2.0μm, 2.5μm, 3μm, 3.2μm and other typical but non-limiting arbitrary point values or interval values between any two point values; particle size D90 can be 2μm, 5μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm, 8μm, 10μm, 11μm and other typical but non-limiting arbitrary point values or interval values between any two point values; particle size D99 can be 3μm, 5μm, 8μm, 10μm, 11μm, Typical but non-limiting arbitrary point values or interval values between any two point values include 11.2μm, 11.3μm, 11.5μm, 11.7μm, 11.9μm, 12.0μm, 12.1μm, 12.3μm, 12.5μm, 12.6μm, 12.7μm, 12.8μm, 12.9μm, 13.0μm, 15μm, 18μm, 20μm, etc.
[0036] In some possible implementations, in the doped phosphate-based positive electrode material, the particle size span of the particles is 1 to 6. The particle size span is calculated using the formula (D90-D10) / D50. The smaller the particle size span, the more uniform the particle size and the higher the size consistency. Exemplarily, in the doped phosphate-based positive electrode material, the particle size span of the particles can be 1, 2, 3, 4, 5, 6, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0037] In the above-mentioned embodiments of the present application, the phosphate-based positive electrode material is doped, and the particles with smaller particle size can shorten the diffusion path of lithium ions in the positive electrode material, which is conducive to the insertion and extraction of lithium ions, thereby improving the rate performance of the battery, that is, the performance of the battery at high charge and discharge rates. In addition, small particles can increase the specific surface area of the active material and increase the number of active sites for the electrochemical reaction, thereby enhancing the electrochemical reaction performance of the battery. Appropriate particle size distribution helps to optimize the energy density of the battery, so that the battery can maintain good cycle stability while maintaining a high energy output. Therefore, in the doped phosphate-based positive electrode material, the particle size D10 of the particles is 0.20μm to 0.80μm, the particle size D50 is 0.8μm to 3.2μm, the particle size D90 is 2μm to 11μm, and the particle size D99 is 3μm to 20μm. Furthermore, when the particle size span (D90-D10) / D50 is in the range of 1 to 6, the positive electrode material can take into account multiple requirements such as battery performance, preparation process and safety, thereby maximizing cost-effectiveness.
[0038] In some possible implementations, the outer surface of the particles of the doped phosphate-based positive electrode material also has a carbon coating layer. In this case, the carbon coating layer can not only improve the structural stability of the doped phosphate-based positive electrode material, but also improve the conductivity of the doped phosphate-based positive electrode material, improve the cycle stability of the doped phosphate-based positive electrode material, improve the stability of the interface between the positive electrode material and the electrolyte, and alleviate the stress caused by volume change.
[0039] In some possible implementations, in the doped phosphate-based positive electrode material, the thickness of the carbon coating layer is 2nm to 10nm. Specifically, the thickness of the carbon coating layer can be 2nm, 4nm, 5nm, 8nm, 10nm, and other typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, the thickness of the carbon coating layer is thin and uniform, which is beneficial to improve the electrochemical properties such as the structure and cycle stability, electronic conductivity, ion diffusion coefficient, and gram capacity of the doped phosphate-based positive electrode material.
[0040] In some possible implementations, the mass percentage of the carbon coating layer in the doped phosphate-based positive electrode material is 0.8% to 2%, and can be 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, or any other typical but non-restrictive point value or an interval value between any two point values. In this case, the content of the carbon coating layer ensures that the carbon material can form a uniform and stable coated carbon layer structure on the surface of the doped phosphate-based positive electrode material, which is beneficial to improve the electrochemical properties of the doped phosphate-based positive electrode material, such as the structure and cycle stability, electronic conductivity, ion diffusion coefficient, and gram capacity.
[0041] In some possible implementations, the doped phosphate-based positive electrode material includes doped lithium iron phosphate. In this case, the iron site of the doped lithium iron phosphate is doped with titanium and molybdenum, which can significantly improve the ionic conductivity and electronic conductivity of the doped lithium iron phosphate, improve the ion diffusion coefficient, and improve the lattice stability, cycle stability, energy density and other properties of the material.
[0042] In some possible implementations, the molar ratio of lithium, iron, titanium, molybdenum and phosphorus in doped lithium iron phosphate is (0.98-1.05):(0.94-0.98):(0.01-0.04):(0.01-0.02):(0.98-1.05). In this case, the doped phosphate-based positive electrode material has excellent ionic conductivity, electronic conductivity, ion diffusion coefficient, cycle stability, energy density and other properties.
[0043] The doped phosphate-based positive electrode material in the above-mentioned embodiments of the present application can be prepared by the following embodiment method.
[0044] In a second aspect, the present invention provides a method for preparing a doped phosphate-based positive electrode material, as shown in the attached Figure 1 As shown, the following steps are included:
[0045] S10. Obtaining a raw material component and a doping metal source for preparing a phosphate-based active material, and preparing a precursor mixture of the raw material component and the doping metal source by a liquid phase method; wherein the doping metal source includes a titanium source and a molybdenum source;
[0046] S20. In an inert atmosphere, the precursor mixture is sintered once, and then crushed and sintered a second time to obtain a doped phosphate-based positive electrode material; under a pressure of 100MPa to 500MPa, the maximum deformation of the particles of the doped phosphate-based positive electrode material is less than 50%, and the reversible deformation is less than 10%.
[0047] The method for preparing a doped phosphate-based positive electrode material in an embodiment of the present application comprises preparing a precursor mixture of raw material components and a doped metal source including a titanium source and a molybdenum source by a liquid phase method, and then sequentially performing a first sintering, a pulverizing and a second sintering treatment in an inert gas to dope the doped metal element into the lattice of the phosphate-based active material, thereby obtaining a doped phosphate-based positive electrode material. In the liquid phase system adopted, the raw materials are fully mixed and the stoichiometry is controllable, which is conducive to the incorporation of the doped metal element into the lattice of the phosphate-based active material. The two sintering and pulverizing processes are beneficial to improving the sintering efficiency, controlling the material particle size and improving the uniformity. The preparation process of the embodiment of the present application is simple and suitable for industrial large-scale production and application. The prepared doped phosphate-based positive electrode material optimizes the structure of the doped phosphate-based positive electrode material, improves the structural stability of the doped phosphate-based positive electrode material, and improves the compression modulus of the positive electrode material by doping metal elements in the crystal structure of the phosphate-based active material. At the same time, it can change the chemical composition and electronic structure of the surface of the positive electrode material, so that the doped phosphate-based positive electrode material has higher ionic conductivity, electronic conductivity, gram capacity, cycle stability and other characteristics.
[0048] In the above step S10:
[0049] In some possible implementations, raw material components for preparing the phosphate-based active material include a lithium source, an iron source, and a phosphorus source.
[0050] In some possible implementations, the doping metal source includes at least one of a vanadium source, a titanium source, a molybdenum source, and a magnesium source.
[0051] In some embodiments, after the lithium source, iron source, titanium source, and doping metal source are dissolved separately, a precursor mixture is prepared by a liquid phase method; then, sintering and pulverizing are performed twice in sequence to obtain a doped lithium iron phosphate material.
[0052] In some possible implementations, the doped metal source includes a vanadium source and a titanium source, and the molar ratio of lithium, iron, titanium, molybdenum and phosphorus in the doped phosphate-based positive electrode material is (0.98-1.05):(0.94-0.98):(0.01-0.04):(0.01-0.02):(0.98-1.05). In this case, the doped phosphate-based positive electrode material has excellent electronic conductivity, ion diffusion coefficient, cycle stability, energy density and other properties.
[0053] In some possible implementations, the processing steps of the liquid phase method include: dissolving the raw material components and the doping metal source in an acidic solution with a concentration of 30% to 45%, and preparing a precursor mixture by autothermal evaporation. In this case, in the liquid phase system, the raw materials are fully mixed and the stoichiometry is controllable, which is conducive to the incorporation of titanium and molybdenum elements into the crystal structure of the phosphate-based active material. In addition, autothermal evaporation uses the solvation energy and reaction heat of the raw materials to evaporate the solvent, reducing the need for external heat sources, which is conducive to cost reduction and energy saving.
[0054] In some possible implementations, the concentration of the acidic solution is 30% to 45%, and the acidic solution includes nitric acid. In this case, the acidic solution has good solubility for both the raw material components and the doping metal source, which is conducive to the self-heating evaporation reaction of the raw material components and the doping metal source in the liquid phase system to obtain a precursor mixture. In some embodiments, the concentration of the acidic solution such as nitric acid can be 30%, 32%, 35%, 36%, 38%, 40%, 42%, 44%, 45%, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0055] In some possible implementations, the titanium source includes at least one of titanic acid, titanate, and titanate ester.
[0056] In some possible implementations, the molybdenum source includes at least one of molybdenum oxide, molybdenum sulfide, molybdate, molybdenum chloride, and molybdenum fluoride.
[0057] In some possible implementations, the vanadium source includes at least one of vanadium oxide, vanadate, and vanadium nitrate.
[0058] In some possible implementations, the magnesium source includes at least one of magnesium oxide, magnesium halide, magnesium nitrate, and magnesium acetate.
[0059] In some possible implementations, the lithium source includes at least one of lithium hydroxide, lithium carbonate, and lithium nitrate.
[0060] In some possible implementations, the iron source includes at least one of ferric nitrate, ferrous oxalate, and elemental iron.
[0061] In some possible implementations, the phosphorus source includes at least one of hydrogen phosphate and orthophosphate.
[0062] The doping metal sources and raw material components used in the above embodiments of the present application are of high purity, and the above components all have good solubility, which is conducive to the preparation of doped phosphate-based positive electrode materials.
[0063] In the above step S20:
[0064] In some possible implementations, the flow rate of the inert atmosphere during the primary sintering process is 50 mL / min to 150 mL / min; specifically, the flow rate of the inert atmosphere can be 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, 100 mL / min, 110 mL / min, 120 mL / min, 130 mL / min, 140 mL / min, 150 mL / min. In some possible implementations, the inert atmosphere includes at least one of nitrogen, argon, and helium. In this case, the inert atmosphere can fully ensure the synthesis of the doped phosphate-based cathode material, avoid the material from being oxidized by high temperature, and improve the crystal structure of the doped phosphate-based cathode material.
[0065] In some possible implementations, the heating rate of the primary sintering is 1°C / min to 5°C / min, the temperature is 500°C to 650°C, and the duration is 10h to 16h. In this case, the primary sintering process is the process of the initial formation of the doped phosphate-based positive electrode material, and the particle size and the discharge of volatile components can be well balanced.
[0066] Exemplarily, the heating rate of the primary sintering can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the holding temperature can be 500°C, 550°C, 600°C, 650°C, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the duration can be 10h, 12h, 14h, 16h, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values.
[0067] In some possible implementations, a carbon source is added during the primary sintering process. In this case, by adding a carbon source during the primary sintering process, it can not only play a reducing role, but also coat the initially formed doped phosphate-based positive electrode material, which is beneficial to adjust the particle size, morphology and other characteristics of the doped phosphate-based positive electrode material. It improves the coating effect of the carbon material on the active material and improves the particle size, specific surface area, morphology and other characteristics of the doped phosphate-based positive electrode material.
[0068] In some possible implementations, the carbon source includes at least one of glucose, fructose, sucrose, methanol, ethanol, and ethylene glycol. These carbon sources can all play a reducing role under sintering conditions, and can preliminarily coat the doped phosphate-based positive electrode material and adjust the particle size, morphology, and other characteristics of the material.
[0069] In some possible implementations, the amount of carbon source added during the primary sintering process is 100 mL / kg to 200 mL / kg. In this case, the carbon content added during the primary sintering process is beneficial to regulating the compaction density, specific surface area, conductivity and other properties of the finished product. Exemplarily, the amount of carbon source added during the primary sintering process can be 100 mL / kg, 110 mL / kg, 120 mL / kg, 130 mL / kg, 140 mL / kg, 150 mL / kg, 160 mL / kg, 170 mL / kg, 180 mL / kg, 190 mL / kg, 200 mL / kg, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0070] In some possible implementations, the flow rate of the inert atmosphere during the secondary sintering process is 50 mL / min to 150 mL / min. Specifically, the flow rate of the inert atmosphere can be 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, 100 mL / min, 110 mL / min, 120 mL / min, 130 mL / min, 140 mL / min, 150 mL / min. In some possible implementations, the inert atmosphere includes at least one of nitrogen, argon, and helium. In this case, the inert atmosphere can fully ensure the synthesis of doped phosphate-based cathode materials, avoid high-temperature oxidation of the materials, and improve the crystal structure of doped phosphate-based cathode materials.
[0071] In some possible implementations, the heating rate of the secondary sintering is 1°C / min to 5°C / min, the temperature is 650°C to 850°C, and the duration is 14h to 20h. In this case, the secondary sintering can make the crystals of the doped phosphate-based cathode material more complete and have a higher crystallinity, and is conducive to improving the graphitization degree of the carbon coating layer.
[0072] Exemplarily, the heating rate of the secondary sintering can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the holding temperature can be 650°C, 700°C, 750°C, 800°C, 850°C, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the duration can be 14h, 16h, 18h, 20h, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values.
[0073] In some possible implementations, a carbon source is added during the secondary sintering process. In this case, the amount of carbon source added during the secondary sintering process is conducive to forming a complete carbon coating layer and improving the morphology of the doped phosphate-based positive electrode material.
[0074] In some possible implementations, the carbon source includes at least one of glucose, fructose, sucrose, methanol, ethanol, and ethylene glycol; these carbon sources can be uniformly coated on the surface of the doped phosphate-based positive electrode material during high-temperature sintering.
[0075] In some possible implementations, the amount of carbon source added during the secondary sintering process is 10 mL / kg to 20 mL / kg. In this case, the carbon content in the doped phosphate-based cathode material can form a complete and uniform coating layer, improve the particle size, specific surface area, morphology and other properties of the doped phosphate-based cathode material, thereby improving the compaction density, active specific surface area, cycle stability and other properties of the doped phosphate-based cathode material, and is also conducive to ensuring the capacity of the doped phosphate-based cathode material.
[0076] Exemplarily, the amount of carbon source added during the secondary sintering process can be 10 mL / kg, 12 mL / kg, 14 mL / kg, 15 mL / kg, 16 mL / kg, 18 mL / kg, 20 mL / kg, or any other typical but non-limiting point value or an interval value between any two points.
[0077] In some possible implementations, in the doped phosphate-based positive electrode material, the particle size D10 of the particles is 0.20 μm to 0.80 μm, the particle size D50 is 0.8 μm to 3.2 μm, the particle size D90 is 2 μm to 11 μm, and the particle size D99 is 3 μm to 20 μm.
[0078] In some possible implementations, in the doped phosphate-based positive electrode material, the particle size span (D90-D10) / D50 of the particles is 1-6.
[0079] In some possible implementations, in the doped phosphate-based positive electrode material, the thickness of the carbon coating layer is 2 nm to 10 nm.
[0080] In some possible implementations, in the doped phosphate-based positive electrode material, the mass percentage of the carbon coating layer is 0.8% to 2%.
[0081] In some possible implementations, under the condition of a pressure of 100 MPa to 400 MPa, the maximum deformation amount of the particles of the doped phosphate-based positive electrode material is 20% to 30%, and the reversible deformation amount is 1.5% to 5%.
[0082] The beneficial effects of the above embodiments of the present application have been discussed above and will not be repeated here.
[0083] In a third aspect, an embodiment of the present application provides an application of a doped phosphate-based positive electrode material, wherein the above-mentioned doped phosphate-based positive electrode material or the doped phosphate-based positive electrode material prepared by the above-mentioned method is applied to a positive electrode sheet and / or a secondary battery.
[0084] The doped phosphate-based positive electrode material provided in the embodiments of the present application has high electronic conductivity, ion diffusion coefficient, crystal structure stability, charge and discharge cycle stability, capacity and other characteristics, and can be directly applied to the positive electrode sheet, and can also be further applied to the secondary battery to improve the charge and discharge specific energy, discharge platform, cycle capacity retention rate, rate performance and other properties of the positive electrode sheet and the secondary battery, and comprehensively improve the battery's kinetic performance and cycle stability.
[0085] In some possible implementations, a positive electrode sheet is provided, including a current collector and a positive electrode active layer formed on the surface of the current collector, wherein the positive electrode active layer contains the above-mentioned doped phosphate-based positive electrode material. In the positive electrode sheet of the embodiment of the present application, since the above-mentioned doped phosphate-based positive electrode material is used in the positive electrode active layer, the electrochemical properties of the positive electrode sheet, such as the charge and discharge specific energy, discharge platform, and cycle capacity retention rate, are improved.
[0086] In some possible implementations, the preparation of the positive electrode active layer includes the steps of: mixing the above-mentioned doped phosphate positive electrode material, conductive agent and binder to form an electrode slurry, coating the electrode slurry on the current collector, and preparing the positive electrode sheet through drying, rolling, die cutting and other steps.
[0087] In some possible implementations, the mass percentage of the doped phosphate-based positive electrode material in the positive electrode active layer of the positive electrode sheet is 93% to 97%. Specifically, the mass percentage of the doped phosphate-based positive electrode material in the positive electrode active material layer can be 93%, 94%, 95%, 96%, 97%, etc.
[0088] In some possible implementations, the current collector of the positive electrode sheet includes but is not limited to any one of copper foil and aluminum foil.
[0089] In some possible implementations, the content of the binder in the active material layer of the positive electrode sheet is 2.5wt% to 3wt%. In specific embodiments, the content of the binder can be 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, etc., which are typical but not limiting contents.
[0090] In some possible implementations, the binder includes one or more of polyvinylidene chloride, polymethyl methacrylate, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.
[0091] In some possible implementations, the content of the conductive agent in the positive electrode active material layer is 0.5wt% to 2.5wt%. In specific embodiments, the content of the conductive agent can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, etc., which are typical but not limiting contents.
[0092] In some possible implementations, the conductive agent includes carbon nanotubes, graphite, carbon black, acetylene black, graphene, carbon fiber, C 60 and one or more of carbon nanotubes.
[0093] In some embodiments, the solvent in the positive electrode slurry includes one of N-methylpyrrolidone, dimethyl sulfoxide, and dimethylformamide, and the content thereof is 35% to 60%.
[0094] In some possible implementations, a secondary battery is provided, wherein the secondary battery comprises the above-mentioned positive electrode sheet. The secondary battery provided in the embodiment of the present application, because it comprises the above-mentioned positive electrode sheet with excellent electrochemical properties such as good stability, high energy density, good rate performance, and good cycle stability, improves the electrochemical properties of the secondary battery such as charge and discharge specific energy, discharge platform, and cycle capacity retention rate.
[0095] In some possible implementations, the preparation of a secondary battery includes the following steps:
[0096] ① The above-mentioned doped phosphate positive electrode material, conductive agent, and positive electrode binder are added to the solvent in sequence, and stirred for 2 hours under a vacuum environment to obtain a positive electrode slurry;
[0097] ②Evenly coat the positive electrode slurry on the aluminum foil with a surface density of 8 mg / cm 2 ~10mg / cm 2 , then bake at 100℃~130℃ for 2h~3h;
[0098] ③Put the aluminum foil loaded with positive electrode material into the roller press; the compaction density of the electrode sheet is 2.0g / cm 3 ~2.5g / cm 3 Cut the rolled positive electrode sheet into discs with a diameter of 14 mm to 16 mm and a thickness of 0.05 mm to 0.10 mm; bake in a vacuum drying oven for 2 h to 3 h;
[0099] ④ Assemble the positive electrode sheet, separator, negative electrode sheet and electrolyte into a secondary battery in a glove box filled with argon gas.
[0100] The present application does not specifically limit the negative electrode sheet, electrolyte, separator, etc. in the secondary battery of the embodiment, and can be applied to any battery system.
[0101] In some possible implementations, the negative electrode active material of the secondary battery includes, but is not limited to, carbon materials such as graphite, soft carbon (such as coke), hard carbon, or nitrides, tin-based oxides, tin alloys, and nano-negative electrode materials, etc. The current collector includes, but is not limited to, any one of copper foil and aluminum foil.
[0102] In some possible embodiments, the steps of making a negative electrode sheet include: mixing a negative electrode active material with a conductive agent such as conductive carbon black, a binder such as carboxymethyl cellulose and styrene-butadiene rubber, and a solvent such as water in a mass ratio of (80-99):(1-5):(2-10):100 to make a negative electrode mixed slurry, vacuum degassing, discharging, coating on a coating machine, and obtaining a negative electrode sheet after rolling, slitting, and die-cutting.
[0103] In some possible implementations, the separator can block the passage of electrons and allow the passage of ions. Exemplarily, the separator includes, but is not limited to, at least one material selected from polypropylene fiber, polyacrylonitrile fiber, polyvinyl formal fiber, poly(ethylene terephthalate), polyethylene terephthalate, polyamide fiber, and poly(p-phenylene terephthalamide).
[0104] In some possible implementations, the electrolyte includes at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], Li[(FSO2)2N], Li[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein m and n are natural numbers. These electrolytic salts can ensure high ionic conductivity of the electrolyte, and do not cause harmful side reactions with electrode materials, electrolytes, diaphragms, etc., and have good chemical stability.
[0105] In some possible implementations, the secondary battery includes at least one of a battery cell, a battery module, and a battery pack.
[0106] In some possible embodiments, the battery cell types include lithium-ion batteries and new batteries such as lithium metal batteries.
[0107] In some possible implementations, the battery cells of the present application can be assembled into a battery module, and the number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Further, the battery module can also include a housing with a storage space, and multiple battery cells are stored in the storage space.
[0108] In a possible implementation, the battery cells and / or battery modules may also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0109] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in performance of the doped phosphate-based positive electrode material and its preparation method and application in the embodiments of the present application, the above technical solution is illustrated by multiple embodiments below.
[0110] Example 1
[0111] A method for preparing titanium-molybdenum dual-doped lithium iron phosphate comprises the following steps:
[0112] 1. 36.95g Li2CO3, 404g Fe(NO3)3·9H2O, 0.798g TiO2, 2.06g Na2MoO4, 97.99g H3PO4, 3.6g C6H 12 After O6 is dissolved in 40% nitric acid solution, the solution is heated until it starts to spontaneously heat up in the reactor, and the external heat source is turned off. After the solution in the system evaporates spontaneously, a precursor is obtained.
[0113] 2. The precursor obtained in step 1 was crushed, and the obtained powder was sintered for the first time in a tube furnace. The nitrogen flow rate was set to 60 mL / min; when the temperature was raised to 500°C (heating rate: 5°C / min), ethylene glycol was introduced at a flow rate of 0.2 ml / min; the temperature was continued to rise to 550°C (heating rate: 3°C / min), and the temperature was kept for 6.5 hours; then the ethylene glycol was turned off and naturally cooled to room temperature to obtain a primary sintered material.
[0114] 3. The primary sintered material obtained in step 2 is crushed, and the obtained powder is sintered for the second time in a tube furnace. The nitrogen flow rate is set to 60mL / min. When the temperature rises to 500°C (heating rate: 5°C / min), ethylene glycol is introduced with a flow rate of 0.02ml / min; the temperature continues to rise to 760°C (heating rate: 3°C / min), and the temperature is kept for 7.5h; then the ethylene glycol is turned off and naturally cooled to room temperature to obtain the secondary sintered material. It is crushed to obtain a finished product of titanium-molybdenum doped lithium iron phosphate material, wherein the doping molar ratio of the titanium element is 0.01, and the doping molar ratio of the molybdenum element is 0.01.
[0115] Example 2
[0116] A titanium-molybdenum dual-doped lithium iron phosphate material, which differs from Example 1 in that the amount of TiO2 added in step 1 is 3.19 g, and the amount of Na2MoO4 added is 4.12 g, so that in the product, the molar ratio of titanium element is 0.04 and the molar ratio of molybdenum element is 0.02.
[0117] Example 3
[0118] A titanium-molybdenum dual-doped lithium iron phosphate material, which differs from Example 1 in that 3.19 g TiO2 is added in step 1, and Na2MoO4 is not added, so that the molar ratio of titanium element in the product is 0.04.
[0119] Example 4
[0120] A titanium-molybdenum dual-doped lithium iron phosphate material, which differs from Example 1 in that 4.12 g Na2MoO4 is added in step 1, and TiO2 is not added, so that the molar ratio of the molybdenum element in the product is 0.02.
[0121] Example 5
[0122] A titanium-molybdenum dual-doped lithium iron phosphate material, which differs from Example 1 in that the amount of TiO2 added in step 1 is 3.99 g, and the amount of Na2MoO4 added is 6.18 g, so that in the product, the molar ratio of titanium element is 0.05 and the molybdenum element is 0.03.
[0123] Example 6
[0124] A titanium-zirconium dual-doped lithium iron phosphate material, which differs from Example 1 in that in step 1, no Na2MoO4 is added, 3.19g TiO2 is added, and 6.54g (CH3COO)2Zr is added, so that in the product, the molar ratio of titanium element is 0.04 and the molar ratio of zirconium element is 0.02.
[0125] Comparative Example 1
[0126] A lithium iron phosphate material, which differs from Example 1 in that no Na2MoO4 and no TiO2 are added in step 1.
[0127] Furthermore, in order to verify the progress of the embodiments of the present application, the following characterizations and tests were performed on each embodiment and comparative example:
[0128] 1. The materials prepared in Example 1, Example 2, Example 3 and Example 4 were tested by electron microscope. The test results are shown in the attached figure. Figure 2 The scanning electron microscope images of Example 1, Example 2, Example 3 and Example 4 are shown as follows:
[0129] As can be seen from Example 3 in the accompanying drawings, titanium doping reduces the particle size, which is beneficial to improving the dynamic performance.
[0130] It can be seen from Example 4 in the attached drawings that molybdenum doping reduces the difference in binding energy of each crystal plane of lithium iron phosphate, causing the particles to grow isotropically and increase roundness.
[0131] As shown in the attached drawings, Example 1 and Example 2 show that after dual doping with titanium and molybdenum, the size of lithium iron phosphate particles is reduced and the roundness is increased, which is beneficial to improving the compaction density. Within the scope of the patent, the more the doping amount, the more the compaction density is improved.
[0132] 2. The crystal structure of the materials prepared in Examples 1 to 4 was tested. The test results are shown in the attached Figure 3 As shown in the X-ray diffraction patterns of Example 1, Example 2, Example 3, and Example 4. It can be seen that compared with pure lithium iron phosphate, the characteristic peak of the 211 crystal plane of the doped material moves to a high angle, and no detectable impurity phase is generated, proving that titanium and molybdenum elements are doped into the lithium iron phosphate lattice structure.
[0133] 3. Particle size: The materials prepared in the above embodiments and comparative examples were tested by laser particle size analyzer to determine the particle size D10, D50, D90, D99 and the particle size span distribution of (D90-D10) / D50;
[0134] 4. The compression modulus of the positive electrode materials prepared in the above embodiments and comparative examples were tested respectively, and the test conditions were: 0MPa~350MPa; the test results are shown in Table 1 below:
[0135] 5. Compaction density test: the test pressure is 3T;
[0136] The test results are shown in Table 1 below:
[0137] Table 1
[0138]
[0139] From the test results in Table 1, it can be seen that after the material prepared in the embodiment of the present application is doped with titanium and molybdenum, the compaction density is increased, the reversible deformation is increased, and the compression modulus is improved. Under the condition of a pressure of 100MPa to 400MPa, the maximum deformation of the particles of the doped phosphate-based positive electrode material prepared in the embodiment of the present application is 20% to 30%, and the reversible deformation is 1.5% to 5%.
[0140] 6. Electrochemical performance test: The finished product of the doped lithium iron phosphate positive electrode material prepared in each embodiment and comparative example was applied to a lithium ion battery. The specific preparation method is as follows:
[0141] ① Take 9.4 g of the finished material prepared in the embodiment or comparative example, 0.3 g of polyvinylidene fluoride, and 0.3 g of carbon black, add them to 10 g of N-methylpyrrolidone solution, and stir in a vacuum stirrer for 2.5 h to prepare a positive electrode slurry;
[0142] ②Evenly coat the positive electrode slurry on the aluminum foil with a surface density of 8.8 mg / cm 2 , then baked at 120℃ for 2.5h;
[0143] ③Put the aluminum foil loaded with positive electrode material into the roller press and roll it; the compaction density of the electrode sheet is 2.2g / cm3. Cut the rolled positive electrode sheet into a disc with a diameter of 14mm and a thickness of 0.06mm; bake it in a vacuum drying oven for 2.5h;
[0144] ④ Assemble the positive electrode sheet, separator (polypropylene film, diameter 18 mm), negative electrode sheet (lithium sheet, diameter 16.5 mm) and 160 μL electrolyte (1 mol / L LiPF6 / EC and DMC mixed in a volume ratio of 1:1) into a button lithium-ion battery in a glove box.
[0145] A. Dynamic test: At room temperature 25°C, constant current charge and discharge tests were performed on each prepared lithium-ion battery at a current density of 1C. The test results are shown in Table 2.
[0146] Table 2
[0147]
[0148] It can be seen from the above test results that titanium doping in Example 3 can improve the ion and electron transfer rate, thereby improving the electrochemical polarization and median voltage difference, and improving energy efficiency. Molybdenum doping in Example 4 can improve the charge and discharge specific capacity of lithium iron phosphate and improve the room temperature kinetic performance. From the test results of Example 1 and Example 2, it can be seen that the charge and discharge specific capacity and coulomb efficiency of lithium iron phosphate are further improved after titanium and molybdenum dual doping, the median voltage difference and the end-of-discharge slope are reduced, and the constant current charge ratio is increased, which proves that the electrochemical polarization is reduced and the kinetic performance is significantly improved. The charge and discharge specific capacity of Example 5 decreases slightly, but is still greater than that of Comparison 1 which is not doped with any elements. Compared with Example 6, the energy density of Example 1 and Example 2 is higher.
[0149] B. Sequential performance test: At high temperature of 45°C, 0.1C charge and discharge for two cycles followed by 1C constant current cycle. The capacity retention rate during high temperature cycle is summarized in Table 3:
[0150] Table 3
[0151] Sample No. Cycle number when capacity retention rate is 95% Cycle number when capacity retention rate is 80% Example 1 206 239 Example 2 221 257 Example 3 178 202 Example 4 166 197 Example 5 185 236 Example 6 161 184 Comparative Example 1 121 132
[0152] It can be seen from the above test results that titanium doping in Example 3 can reduce electrochemical polarization and improve energy efficiency, thereby improving the capacity retention rate during cycling. Molybdenum doping in Example 4 can improve the isotropic and reversible deformation of lithium iron phosphate, thereby better alleviating the volume change of particles caused by the insertion and extraction of lithium ions, and maintaining the structural stability of the material during cycling. From the test results of Example 1, it can be seen that after co-doping with molybdenum and titanium elements, the energy density is improved, the capacity retention rate is improved, and the cycle decay is slower. The high-temperature cycle performance of Example 2 is further improved, which is the best ratio. The decay rate of Example 5 is slightly faster in the early stage of the cycle, but the decay rate slows down in the later stage, and the overall capacity retention rate is still better than that of Example 6 and Comparative Example 1. Comparative Example 1, which is not doped with any elements, has the fastest cycle decay and the worst high-temperature cycle performance.
[0153] Through the above-mentioned electrochemical performance test, it can be known that the phosphate-based positive electrode material prepared by doping in the embodiment of the present application has a maximum deformation of 20% to 30% and a reversible deformation of 1.5% to 5% under a pressure of 100MPa to 400MPa. Within this parameter range, the electrochemical performance of the phosphate-based positive electrode material can be better improved.
[0154] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A doped phosphate-based positive electrode material, characterized in that: It comprises a phosphate-based active material and a doped metal element doped in the crystal structure of the phosphate-based active material; under a pressure of 100MPa to 500MPa, the maximum deformation of the particles of the doped phosphate-based positive electrode material is less than 50%, and the reversible deformation is less than 10%.
2. The doped phosphate-based positive electrode material according to claim 1, characterized in that: The doping metal element includes at least one of V, Ti, Mo, and Mg; And / or, under the condition of a pressure of 100 MPa to 400 MPa, the maximum deformation amount of the particles of the doped phosphate-based positive electrode material is 20% to 30%, and the reversible deformation amount is 1.5% to 5%.
3. The doped phosphate-based positive electrode material according to claim 2, characterized in that: The doped metal elements include titanium and molybdenum; The phosphate-based active material contains iron, and the doping metal element is doped in the iron site of the phosphate-based active material.
4. The doped phosphate-based positive electrode material according to claim 3, characterized in that: In the iron element site of the doped phosphate-based positive electrode material, the molar ratio of iron element, titanium element and molybdenum element is (0.94-0.98):(0.01-0.04):(0.01-0.02); In the doped phosphate-based positive electrode material, the particle size D10 of the particles is 0.20 μm to 0.80 μm, the particle size D50 is 0.8 μm to 3.2 μm, the particle size D90 is 2 μm to 11 μm, and the particle size D99 is 3 μm to 20 μm; And / or, in the doped phosphate-based positive electrode material, the particle size span of the particles is 1 to 6.
5. The doped phosphate-based positive electrode material according to any one of claims 1 to 4, characterized in that: The outer surface of the particles of the doped phosphate-based positive electrode material also has a carbon coating layer; And / or, the doped phosphate-based positive electrode material includes doped lithium iron phosphate.
6. The doped phosphate-based positive electrode material according to claim 5, characterized in that: In the doped phosphate-based positive electrode material, the thickness of the carbon coating layer is 2 nm to 10 nm; And / or, in the doped phosphate-based positive electrode material, the mass percentage of the carbon coating layer is 0.8% to 2%; And / or, in the doped lithium iron phosphate, the molar ratio of lithium element, iron element, titanium element, molybdenum element and phosphorus element is (0.98-1.05):(0.94-0.98):(0.01-0.04):(0.01-0.02):(0.98-1.05).
7. A method for preparing a doped phosphate-based positive electrode material, characterized in that: The following steps are involved: Obtaining raw material components and a doping metal source for preparing a phosphate-based active material, and preparing a precursor mixture by a liquid phase method using the raw material components and the doping metal source; In an inert atmosphere, the precursor mixture is sintered once, and then crushed and sintered twice to obtain a doped phosphate-based positive electrode material; Under the condition of a pressure of 100MPa to 500MPa, the maximum deformation amount of particles of the doped phosphate-based positive electrode material is less than 50%, and the reversible deformation amount is less than 10%.
8. The method for preparing a doped phosphate-based positive electrode material according to claim 7, characterized in that: The raw material components for preparing the phosphate-based active material include a lithium source, an iron source and a phosphorus source; And / or, the doping metal source includes at least one of a vanadium source, a titanium source, a molybdenum source, and a magnesium source; And / or, the primary sintering has a heating rate of 1°C / min to 5°C / min, a temperature of 500°C to 650°C, and a duration of 10h to 16h; And / or, the secondary sintering has a heating rate of 1°C / min to 5°C / min, a temperature of 650°C to 850°C, and a duration of 14h to 20h; And / or, the flow rate of the inert atmosphere during the primary sintering and the secondary sintering is independently 50 mL / min to 150 mL / min; And / or, a carbon source is added during the primary sintering and the secondary sintering; And / or, under the condition of a pressure of 100 MPa to 400 MPa, the maximum deformation amount of the particles of the doped phosphate-based positive electrode material is 20% to 30%, and the reversible deformation amount is 1.5% to 5%.
9. The method for preparing a doped phosphate-based positive electrode material according to claim 8, characterized in that: The doped metal source includes a vanadium source and a titanium source; in the doped phosphate-based positive electrode material, the molar ratio of lithium, iron, titanium, molybdenum and phosphorus is (0.98-1.05):(0.94-0.98):(0.01-0.04):(0.01-0.02):(0.98-1.05); And / or, the carbon source comprises at least one of glucose, fructose, sucrose, methanol, ethanol, and ethylene glycol; And / or, the amount of carbon source added during the primary sintering process is 100 mL / kg to 200 mL / kg; And / or, the amount of carbon source added during the secondary sintering process is 10 mL / kg to 20 mL / kg.
10. An application of a doped phosphate-based positive electrode material, characterized in that: The doped phosphate-based positive electrode material according to any one of claims 1 to 6 or the doped phosphate-based positive electrode material prepared by the method according to any one of claims 7 to 9 is applied to a positive electrode sheet and / or a secondary battery.
Citation Information
Cited By
Doped phosphate-based positive electrode material, and preparation method therefor and use thereof
WO2026086101A1